Analysis of Support Vector Machine (SVM) Method and Simple Additive Weighting (SAW) Method in Making Decisions to Choose Specialization - Stevanny Tamaela; Yopi Andry Lesnussa; Venn Y.I. Ilwaru; Abdul Malik Balami (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2020)
The Specialization of students is a learning based on the interests of students according to learning opportunities that exist in educational units. Providing education in high school education units based on the 2013 curriculum there is a program for determining specialization for high school students held in class X. Specialization in the 2013 curriculum in high schools is the specialization group for Natural Sciences and Social Sciences. This study uses the Support Vector Machine (SVM) method and the Simple Additive Weighting (SAW) method which aims to compare the accuracy of each method in Decision Making (SPK) specialization program in the Natural Science and Social Sciences at SMA Negeri 1 Ambon. From the research results, the results of the specialization selection from the SAW method differ from the real data, while the results of the SVM method show the same results as the selection of real specialization in SMA Negeri 1 Ambon